The Role of Parents in DEveloping Religious and Moral Values in Early Childhood during the Covid-19 Pandemi at RT 12 RW 05 Oebelo Village, Central Kupang District, Kupang Regency - Selvi Regina Bria; Margareta P.E. Djokaho; Sartika Kale (Universitas Nusa Cendana, 2023)
ABSTRACTReligious and moral values ​​of children during the COVID-19 pandemic in RT 12 RW 05, Oebelo Village, Central Kupang District, Kupang Regency. For this reason, this study aims to find out more about the role of parents in developing children's religious and moral values ​​during the COVID-19 pandemic in RT 12 RW 05, Oebelo Village, Central Kupang District, Kupang Regency which is considered to have not optimal religious and moral values, so it can be seen as far as possible. which is the role of parents in developing children's religious and moral values. The informants in this study were 6 parents of children aged 5-6 years. Data were taken using observation and interview techniques. The results, namely the religious and moral values ​​of children aged 5-6 years in RT 12 RW 05, Oebelo Village, Central Kupang District, Kupang Regency were carried out in three steps, namely introducing religion to children, teaching children to worship and instilling respect and courtesy to children.Keywords: parental role; religious and moral values; covid-19 pandemic; early childhood